PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN COOPERTIVE TIPE TEAM PAIR SOLO - fathiah . (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
This research was conducted at Indra Makmu 2 Public Middle School for 3 months in the odd semester of the 2017/2018 school year which aims to improve student learning outcomes. The research subjects were all class VII students, amounting to 30 people, with 11 men and 19 women. In collecting data, researchers used instruments or data collection techniques in the form of granules of test questions totaling 10 items and observation sheets. After the data is collected the researcher conducts data processing and analysis by comparing the results of tests and observations from the initial conditions, the first and second cycles. The results showed an increase in completeness of students in the first cycle to 63% (19 students) from the initial condition which was only 17% (5 students), and at the end of cycle II completeness increased again to 87% (24 students).